ปัจจัยและแนวทางในการขับเคลื่อนการดำเนินงานนิเทศภายในโรงเรียนมัธยมศึกษาขนาดเล็กสังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - ปกรณ์พงศ์ อินทองแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this research were: 1) to study factors of the operation of in-school supervision for small secondary schools; 2) to propose guidelines for propelling factors of the operation of in-school supervision for small secondary schools under the Office of the Basic Education Commission. The sample consisted of 285 small secondary schools under the Office of the Basic Education Commission; the 855 respondents, including school director, deputy director of the academic department, and head of in-school supervision; 13 interviewees. The research tools were questionnaires and structured interviews. The data were analyzed by mean, percentage, standard deviation, and content analysis. The results revealed that overall factors of the operation of in-school supervision for small secondary schools under the Office of the Basic Education Commission were at a high level, of which their mean was 4.09. The factor that had the highest mean was the human resources factor, which its mean was 4.13 and, it was a high level, followed by the motivation factor, which its mean was 4.08, and it was a high level, and the factor of administration, which its mean was 4.06, and it was a high level, respectively. The guidelines for propelling the factors of the operation of in-school supervision for small secondary schools under the Office of the Basic Education Commission are the following guidelines. The guidelines for propelling human resources factor are planning supervision plans in the annual action plan; using peer supervision technique; selecting personnel who have interpersonal skills to perform in-school supervision; assigning teachers to engage with a PLC (Professional Learning Community) in order to provide them to exchange their experience and reflect their problems and cooperate to solve the problems. The guidelines for propelling motivation factor are supporting teachers build good relationships among teachers in order to provide them to consult and communicate together; holding regular meetings; praising and honoring teachers who have works according to occasions in the meeting; encouraging them by praising and congratulating to them; imposing clear policies and work objectives by administrators: assigning work according to each teachers’ aptitude, knowledge, and ability. The guidelines for propelling the administration factor are managing the structure to be decentralized to 4 departments in order to make in-school supervision achieve: an academic department mainly performs in teaching; supporting teachers to realize the significance of in-school supervision and participate in in-school supervision; focusing on in-school supervision by administrators: appointing a supervisory committee responsible for monitoring in-school supervision.